NASKAH PUBLIKASI IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 19 TAHUN 2011 TENTANG RETRIBUSI PERIJINAN TERTENTU DI KECAMATAN TENGGARONG - Akhmad Arisandy (Universitas 17 Agustus 1945 Samarinda, 2014)
AbstrakAkhmad Arisandy, Implementation of Regency Regulation Number 19 Year 2011 on Licensing of Certain additional item in Kutai Kartanegara. Under the guidance of Mrs. Kunti Widayati, S.H.,M.Hum as first mentors and Mrs. Isnawati S.H.,M.H as second mentors. The purpose of this study is to investigate the implementation of In Kutai Kartanegara's Regency Regulation Number 19 Year 2011 on Licensing of Certain levies related Fishing Permits in Tenggarong District and to find out how the implementation as well as obstacles in the implementation of regional regulation. Location of this study is a freshwater aquaculture in Tenggarong District. By using a snowball sampling technique, this study starts by taking a fishery in the Tenggarong district as samples or sources by collecting data using interviews. From the results of field studies on the implementation of In Kutai Kartanegara's Regency Regulation Number 19 Year 2011 on Licensing of Certain levies related Fishing Permits in Tenggarong District was never implemented in the fishery business activities of the fishery to Dinas Kelautan dan Perikanan of Kutai Kartanegara regency , because all parties in it are not aware of any regional regulation. Then the regulation has no constraint for never implemented, but the main obstacle comes precisely from the beginning or source relevant local rulemaking authority delegation that occurred prior to implementation. Local regulations should not be made a mere formality or left floating without delegation of authority or duty, then stakeholders should make a rule to go through a public consultation so that rules are made can be implemented either Keywords: Licensing of Certain additional item, Fishing Permits.